Pathophysiological roles of ERα in the ER signaling mediated oncogenesis of breast cancer - Neja, Sultan Abda (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Estrogen receptors (ER) are members of nuclear receptors that act in the ER signaling pathway regulating the pathophysiology of hormone-responsive target cells including breast tissue. Aim. This detailled review literature was written on the pathophysiology of ER signaling as well as the effect altered ERα and associated pathway derangement in the oncogenesis of breast cancer. Material and methods. This review was performed according to systematic literature search of three major bibliographic databases (Scopus, PubMed, and Cochran). Analysis of the literature. In this pathway, estrogen receptor alpha (ERα) is a key estradiol-17β (E2) induced transcription factor that has been implicated in the initiation and development of the major fraction of breast cancers. Hence understanding the ERα-mediated ER signaling that results in alterations from normal phenotypic features of breast tissue to the oncogenic features of breast cancer is important. The oncogenic effect of ERα in ER signaling is driven by combinations of molecular assets within the cancer cells. Normally, the transcriptional activity of ERα is controlled by tight regulation of its protein level inside the cells. Altered stability and activity of ERα due to its phosphorylation, ubiquitination, glycosylation, sumoylation, and acetylation events can trigger oncogenic ER signaling. Conclusion. The function and activity of ERα is also modulated by its interaction with coregulators as well as crosstalk with oncogenic factors from other oncogenic pathways. These all events increase the complexity of the progression of ER+ breast cancer and its response to endocrine therapy.
Keywords: breast; cancer; estrogen receptor alpha; oncogenesis